The relationship between entrepreneurs knowledge and performance - Tambunan, Damelina Basauli; Hashim, Norashidah (2017)
The purpose of this research is to find out the relationship between entrepreneur knowledge and performance of small medium family-owned business in East Java Indonesia.A total of 381 small medium family-owned businesses in the East Java province of Indonesia are used as research respondents. These respondents were selected using proportional cluster random method to ensure that all of the predetermined areas in East Java were proportionally represented.Confirmatory Factor Analysis (CFA) is used to test the validity of the research variables, whereas Composite (Construct) Reliability is used to test the reliability of the variables. After all variables were declared as valid and reliable, the following step was to perform a multivariate analysis which involved normality, singularity, and outlier tests.After all the multivariate assumptions were fulfilled, a structural model testing was performed using the covarian-based structural model of AMOS. The result of this research suggests that entrepreneur orientation has a positive and significant influence on performance of SMEs.